PENGARUH PENGUNGKAPAN LINGKUNGAN TERHADAP MARKET VALUE PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Dyas Ariyani Putri; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2019)
The objective of this study are to examine: (1) The impact of environmental disclosure on market value (2) The impact of environmental disclosure on market value with corporate governance as the moderating variable. The sample of this study consists of 51 observations from non-financial companies listed in Indonesia Stock Exchange from 2015-2017. Multiple regression analysis is used to test the hypothesis in this research.The result showed that in Indonesia, environmental disclosure activities had a significant influence towards market value. This research also includes several corporate governance aspects as moderating variables were the size of the board of commissioners is proven to moderate this relationship. But, the independent board of commissioners has no significant influence on the relationship between environmental disclosure and market value.